TOURISTS' PERCEPTIONS OF AMED TOURISM VILLAGE, KARANGASEM - Launingtia, I Gusti Ayu Niken (JURNAL KEPARIWISATAAN, 2025)
The aim of this research is to find out the perceptions of tourists who travel to the tourist village of Amed, Karangasem so that tourism actors/local communities can work together in creating a strategy to improve tourist villages in the Amed, Karangasem area. The method in this research uses a qualitative method which will be obtained from the results of observations before conducting research in the Amed tourist village, the results of questionnaires to tourists and also interviews conducted with the aim of sharpening the research results obtained. The factors that most influence tourists' perceptions of Amed Tourism Village are the beauty of its beaches for diving and snorkeling (88.2%), the friendliness of the local community (90.1%), and the cleanliness of the environment (63.4%).